Finding their way again: the experiences of gang-affected refugee youth - Fast, Matthew (Fernwood Publishing, 2017)
"Ongoing protracted conflicts in various regions of the world have led to annual increases in the number of people living in refugee situations. Increasingly, Winnipeg, Manitoba, Canada is becoming home to many of these refugees. Refugees, and in particular refugee young people, are vulnerable as they face challenges integrating into their new environment (Kanu, 2008; Rossiter & Rossiter, 2009; Sersli, Salazar, & Lozano, 2010). As well, refugee young people are exposed to various forms and degrees of violence, that can have negative consequences for their personal development (Kaplan, 2009; Rossiter & Rossiter, 2009; Sersli et al., 2010). If positive support mechanisms are insufficient, and if their basic human needs cannot be satisfied, refugee young people become at-risk of involvement in antisocial behaviour and criminal activity (Chekki, 2006; Kanu, 2008; Rossiter & Rossiter, 2009; Sersli et al., 2010). Young people's experience as refugees living in a new milieu informs their perceptions, attitudes, and behaviour. Using a qualitative research method, this book explores the perceptions, challenges and experiences of young adult war-affected refugees who became gang involved after settling in Winnipeg, Manitoba, Canada."--